Upaya Guru dalam Menanamkan Dimensi Bergotong Royong pada Siswa Kelas IV SDN 02 Grawan - Nikmah, Siti Durotun; Wardana, M. Yusuf Setia; Purnamasari, Iin (Pena Edukasia, 2023)
The background that prompted the conduct of this research was the presence of character problems, namely decreased student mutual cooperation behavior, marked by decreased concern among students and lack of cooperation. Teachers can apply various habits in order to increase the dimensions of mutual cooperation in grade IV students. The goal to be achieved in this study is to analyze the teacher's efforts in instilling the dimensions of mutual cooperation in fourth grade students at SDN 2 Grawan. This type of research uses a qualitative descriptive approach. Data collection techniques in this study used observation, interviews, and documentation. Data analysis techniques use the Miles and Huberman models. The results of this study are that the teacher's efforts in instilling the dimensions of mutual cooperation contained in the Pancasila Student Profile are through clean Friday activities which become a routine for students every week, then carry out daily cleaning picket assignments, group learning activities carried out with the teacher. In the process of cultivating the dimensions of mutual cooperation, teachers still find difficulties, namely the lack of supporting media or infrastructure and dealing with students with different characters. However, the researchers assessed that the efforts made by the teacher were able to increase the dimensions of mutual cooperation, namely concern for the environment and student collaboration.